Error analysis in academic writing: a case of international postgraduate students in Malaysia - Amiri, Fatemeh (Australian International Academic Centre, 2017)
This paper examines the different types of writing errors performed by 16 international postgraduate students undertaking an intensive English course at a public university in Malaysia. It was mandatory for international postgraduate students who obtained less than IELTS Band 6 to undertake an Intensive English Course (IEC) offered by the University, prior to entering their respective faculties’ academic programs. The students were required to write a 3-5 page term paper assignment on a topic related to their field of study. Mixed methodology approach was employed to examine and analyze corpus of students’ term papers. The errors in the term papers were identified and classified accordingly. The results of the study revealed that four most common English language errors committed by the participants were sentence structure, articles, punctuation and capitalization. This study also shed light on the manner in which students assumed the rules of English to that of their native language. Such insight is useful for both instructors and students because it provides significant information on the building blocks experienced by English language learners in academic writing.